Plasma Fibrinolytic Activity Following Oral Anabolic Steroid Therapy - Walker, I. D; Davidson, J. F; Young, P; Conkie, J. A (Thrombosis and Haemostasis, 1975)
Six anabolic steroids were assessed for their ability to enhance plasma fibrinolytic activity in males with ischaemic heart disease. Five 17α-alkylated steroids (Ethyloestrenol, Norethandrolone, Methandienone, Methylandrostenediol and Oxymetholone) were examined and all produced a significant increase in plasma plasminogen activator as measured by the euglobulin lysis time. The only non-17α-alkylated steroid studied (Methenolone acetate) failed to enhance fibrinolysis. The 17α-alkylated steroids studied all deserve more detailed evaluation of their long term effects on plasma fibrinolytic activity.